2015
DOI: 10.1007/s12187-015-9341-3
|View full text |Cite
|
Sign up to set email alerts
|

Paths to Positive Development: a Model of Outcomes in the New Zealand Youth Transitions Study

Abstract: This study examined predictors of positive developmental outcomes, including: life satisfaction; optimism; educational achievement; civic engagement; and positive peer influence; in a sample of young people comprised of a study group (n=593) facing significant challenges and a comparison group (n=778) who were progressing more normatively. The study modelled the demographic, risk, and resource predictors of positive outcomes across both groups, and compared the fit of the model across groups using integrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…It could also be argued that the focus on vulnerable youth only produces validity threats due to range restriction in results. However, elsewhere, analyses from this research programme (Boden et al ., ) have demonstrated that any threat to validity posed by model misspecification is not a critical concern for research using this dataset. Finally, the measures used were based on self‐report, and may be subject to errors and biases arising from these methods.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be argued that the focus on vulnerable youth only produces validity threats due to range restriction in results. However, elsewhere, analyses from this research programme (Boden et al ., ) have demonstrated that any threat to validity posed by model misspecification is not a critical concern for research using this dataset. Finally, the measures used were based on self‐report, and may be subject to errors and biases arising from these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Nettle et al report that their meta-analysis revealed evidence of gender differences, such that the association applied for females but not for males, but was unable to detect any differences related to age or other major group difference (such as ethnicity). Although it may be difficult to design a single study that can adequately test all plausible group differences in the association between food insecurity and obesity, the use of nested designs or multigroup analyses (Boden et al 2015;Boden et al 2016;Fergusson et al 2008;Muthén & Muthén 1998 allows the fitting of models across groups and permits tests of the equivalence of model fit across these groups, using only a single model. Multiple tests of groups' differences may be applied to a single model as well.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…For Indigenous students, gaining an education is more difficult because they are separated from their traditional country, from family and community support and are immersed in new cultural and social expectations. Positive family connections are a critical protective factor for successful transitions to adulthood (Boden et al, 2016). The data reported in this paper show that the resilience measures, along with psychological and well-being indicators are affected by the transitions students navigate.…”
Section: Discussionmentioning
confidence: 69%
“…This is a group of students that reported their family did not know much about them, and they were less likely to feel socially connected to their peers. Family and community connections are a key contributor to student resilience (Boden et al, 2016). More re-engaging students had been in contact with the police, or had legal issues.…”
Section: Discussionmentioning
confidence: 99%